Temporal Dynamics of Reproduction of the Neotropical Fish, Crenicichla menezesi (Perciformes: Cichlidae) - Andréa Soares de Araújo; Wallace Silva do Nascimento; Maria Emília Yamamoto; Sathyabama Chellappa (The Scientific World Journal)
The reproductive biology and the gonadal development cycle of the Neotropical cichlid fish, Crenicichla menezesi, is described. This species exhibits sexual dimorphism only during the spawning season. First sexual maturity of females is attained earlier than the males. Both macroscopic and histological investigations of ovaries and testes revealed four stages of gonadal maturation. Mean batch fecundity of females was 372 (±10,41) of mature oocytes. This species is a partial spawner, with an extended spawning period. Monthly values of GSI and the condition factor are negatively correlated during the gonadal development cycle of this species.